Creativity and the arts with young children - Isbell, Rebecca T.; Raines, Shirley C. (Wadsworth, Cengage Learning, 2013)
Includes information about artistic development, children's books, creative drama, movement, musical development, musical instruments, physical development, play, puppetry, recipes, singing, children with special needs, tools and materials, two dimensional art, etc